2019
DOI: 10.3389/fneur.2019.01141
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Sound-Based Interventions on Motor Behavior After Stroke: A Systematic Review

Abstract: Objective: To investigate the effects of sound-based interventions (SBIs) on biomechanical parameters in stroke patients.Methods: PubMed/Medline, Web of Science, the Physiotherapy Evidence Database (PEDro), and the Cochrane Library were searched until September 2019. Studies examining the effect of SBIs on kinematic, kinetic, and electromyographic outcome measures were included. Two independent reviewers performed the screening, and data extraction and risk-of-bias assessment were conducted with the PEDro and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Although previous studies on the effect of acoustic feedback have shown positive effects (Thaut et al, 1996;Aruin et al, 2003;Schmitz et al, 2014;Bella et al, 2015Bella et al, , 2018Park et al, 2015;Shin et al, 2015;Young et al, 2016;Dotov et al, 2017;Ghai et al, 2018;Chang et al, 2019;van Criekinge et al, 2019), clear evidence in patients undergoing gait rehabilitation with orthopedic diseases or (neurologically) healthy individuals is still lacking at the current time. In this context, (Yang et al, 2012) investigated the influence of acoustic error feedback during walking on three unilateral transtibial amputated patients.…”
Section: Discussionmentioning
confidence: 98%
“…Although previous studies on the effect of acoustic feedback have shown positive effects (Thaut et al, 1996;Aruin et al, 2003;Schmitz et al, 2014;Bella et al, 2015Bella et al, , 2018Park et al, 2015;Shin et al, 2015;Young et al, 2016;Dotov et al, 2017;Ghai et al, 2018;Chang et al, 2019;van Criekinge et al, 2019), clear evidence in patients undergoing gait rehabilitation with orthopedic diseases or (neurologically) healthy individuals is still lacking at the current time. In this context, (Yang et al, 2012) investigated the influence of acoustic error feedback during walking on three unilateral transtibial amputated patients.…”
Section: Discussionmentioning
confidence: 98%
“…Despite potential differences in the mechanism of action for music-based rhythmic auditory stimulation and conventional physiotherapy [ 15 , 28 , 29 ], the goal of music-based RAS alone and in combination remained the same: to improve gait and balance after stroke [ 8 , 14 , 28 , 30 ]. A possible explanation might be related to the lack of precision in the Tinetti test to measure gait parameters and the quality of walking in the aftermath of stroke [ 14 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It should be taken into account that the control group also attended an intensive rehabilitation unit, performing 11 h of physiotherapy and 7 h of occupational therapy per week, compared with control groups of other studies that only received an average of 3–5 h/week. This undoubtedly has value for rehabilitation but possibly reduces the comparative effect with the intervention group [ 10 , 15 , 34 ]. Another possible cause could be that we could not evaluate the Timed Up&Go and Tinetti scores in those participants who were unable to walk at baseline (more than 80% in each group).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations